Respuesta :

Answer:

[tex]-\frac{5}{6}[/tex]

Step-by-step explanation:

  1. Write it out: [tex]-\frac{2}{3}[/tex] × [tex]\frac{5}{4}[/tex]  
  2. 3 × 4 = 12
  3. -2 × 5 = -10
  4. Put them together: [tex]-\frac{10}{12}[/tex]  
  5. Simplify: -10/12 = -5/6

I hope this helps!

Answer:

[tex]\frac{-10}{12} ,\frac{-5}{6}[/tex]

Step-by-step explanation:

Start with:

[tex]\frac{-2}{3}[/tex] × [tex]\frac{5}{4}[/tex]

Multiply your numerators.

[tex](-2)(5)=-10[/tex]

Now, multiply your denominators.

[tex](3)(4)=12[/tex]

Let's transfer those numbers into a fraction.

[tex]\frac{-10}{12}[/tex]

You may need to simplify.

Divide by the greatest common factor. In this case, that would be [tex]2[/tex].

[tex]-10[/tex] ÷ [tex]2=-5[/tex]

[tex]12[/tex] ÷ [tex]2=6[/tex]

Put those numbers back into the fraction.

[tex]\frac{-5}{6}[/tex]